Contemporary theories of learning learning theorists -- in their own words - Illeris, Knud (Routledge, 2009)
A collection of some of the most influential learning theorists. It collects chapters that explain both the complex frameworks in which learning takes place and the specific facets of learning, such as the acquisition of learning content, personal development, and the cultural and social nature of learning processes.